(untitled) - LADO, ROBERT (USA, 1978)
1.Identifying a person / 2.Prepositions - of place / 3.More prepositions and prepositional phrases / 4.Position of prepositional phrases / 5.One and ones as noun substitutes / 6.With in questions / 7.A trip to seattle / 8.Contrast either and ether / 9.Getting exercise / 10.Statements with verb more to infinitive / 11.Other sentences with verb more to infinitive / 12.Traveling by train / 13.Plannig summer trip / 14.How many and how much with count and mass nouns / 15.Units of measure with mass nouns / 16.There more be to indicate existence / 17.Planning to buy groceries / 18.Sound right / 19.Helping someone / 20.The modal auxiliary can / 21.The meanings of the modal auxiliaries will may might / 22.Statements in the affirmative and negative and yes no questions with the modal auxiliaries will may migth / 23.The modal auxiliary shall / 24.Scrabble / 25.Contrast light and rigth / 26.Planning for a visit / 27.The modal auxiliaries should and must / 28.Information questions with modal auxiliaries / 29.Information questions about the subject / 30.Questions with why and answers with because / 31.Fire / 32.Sound phone / 33.On the telephone / 34.The expression would like to / 35.Past meaning of the modal auxiliary could / 36.Polite request meaning of the modal auxiliary could / 37.Had to / 38.Mustn't and don't have to / 39.Irregular past with the sound /40.One way to stay healthy / 41.Sound foot / 42.At home after a trip / 43.Possesive pronouns / 44.Ordinal numbers / 45.Use of any some / 46.Irregular past with the sound / 47.Food / 48.Sound Paul / 49.Asking for information / 50.Indefinite pronouns combining some , any , every , and no , with-body and one / 51.Indefinite pronouns combining some , any , every , and no with thing and where / 52.Irregular past with the sound / 53.Leisure time activities / 54.Sound pain / 55.Buying something for another person / 56.Comparison with like the same as different from / 57.Comparison with the same as as as / 58.Idiomatic expressions with as as like / 59.Comparatives of adjetives with more than / 60.Comparatives of adjetives with er than / 61.Spelling and forms of adverbs / 62.Comparison of adverbs with more than er than than / 63.Tourism / 64.Sound pan / 65.Finding the best and the least expensive / 66.Superlatives with the most with adjetives and adverbs / 67.Superlatives with the est / 68.Irregular comparatives and superlatives / 69.Comparison with less and the least / 70.Birthday celebration / 71.Sound socks
Incluye indice analitico pag.195
Keywords: INGLES